Influence of dentin depth on microtensile bond strength of total etching and self-etching adhesive systems - Cecchin, Doglas (2008)
Purpose: The aim of this study was to evaluate the microtensile bond strength of one monocomponent adhesive system (Single Bond – SB) and one self-etching adhesive system (XENO III – XN) in superficial (SD) and deep (DD) dentin. Methods: The occlusal surface of twenty sound human molars was sectioned in two levels: 1mm (SD) and 3mm (DD) below the cusps. The teeth were divided into four groups: G1 (control 1): SB and SD dentin, G2 (control 2): SB and DD dentin, G3: XN and SD dentin, and G4: XN and DD dentin. One composite block was built over these surfaces. The teeth were sectioned into four slabs, which were trimmed to hourglass-shaped specimens (n=20 specimens/group). Each specimen was subjected to microtensile bond testing at a crosshead speed of 0.5mm/min. Data were analyzed by ANOVA and Newman Keuls test. Results: Means (standard deviation) values were (in MPa): G1 = 15.84 (4.04)a; G2 = 13.84 (3.52)a; G3 = 8.76 (1.61)b; G4 = 8.64 (3.12)b. Conclusion: It may by concluded that different depth levels of dentin do not affect bond strength for the same material; SB showed the highest bond strength values in both dentin depths. Key words: Bonding agents; microtensile bond test; dentin depth